Suffering and happiness in Turkish folk poetry in the context of positive psychology: The examples of Asik Mahzuni Serif and Neset Ertas - Güven, Ahmet Zeki; Arslan, Gökmen (Frontiers in Psychology, 2023)
Previous research on happiness has often focused on measuring and comparing it between countries and cultures. However, the widespread adoption of positive psychology at the beginning of the century has fortified the scholarly foundations of “happiness.” In the humanistic approach in particular, the idea of maintaining one’s existence without coming into conflict with society and dissolving one’s own self in it has contributed to the rise of positive psychology in humanism. Thus, communities focus on “happiness” rather than “suffering” in boosting the joy of life within positive psychology, aiming for individuals to achieve peace with themselves and society. This study aimed to explore suffering and happiness in Turkish folk culture in terms of positive psychology through a sample of poems by Asik Mahzuni Serif and Neset Ertas. Since Turkish folk poetry has accumulated a broad spectrum of works over the centuries, only works by these two famous poets were selected as a sample. Folk poets may be thought of as ambassadors voicing the feelings of the public; thus, sometimes they reveal things happening to people and sometimes they advise people about the good. In this qualitative study, the selected poems were subjected to document analysis. The researcher went through all the poems twice and classified them under the themes of suffering and happiness. Then, codes and their frequencies were determined within these themes. The findings revealed suffering and happiness in the poems by Mahzuni and Ertas in the context of positive psychology.